Otx2 mRNA expression is downregulated following traumatic brain injury in zebra finches - Talwalkar, Adam; Duncan, Kelli A. (Frontiers in Neural Circuits, 2025)
Traumatic brain injury (TBI) induces a wide range of neurodegenerative symptoms, yet effective treatment strategies remain limited. Emerging evidence suggests that post-TBI recovery recapitulates aspects of early brain development, highlighting the potential for developmental molecular mechanisms to inform therapeutic interventions. The transcription factor Otx2 is critical for early brain and sensory organ development, as well as the maintenance of retinal and neural function in adulthood. Notably, the transfer of Otx2 homeoprotein into parvalbumin-expressing (PV+) GABAergic interneurons is essential for opening and closing critical periods of plasticity across vertebrates. Here, we investigate the acute regulation of Otx2 mRNA following TBI in adult zebra finches (ZF) to evaluate its potential as a target for future study and therapeutic manipulation in neural repair. Adult ZFs sustained unilateral hemispheric brain injuries, and qPCR was used to quantify Otx2 mRNA expression at 24 hours and 1 week post-injury in both males and females. Our findings reveal a significant downregulation of Otx2 mRNA expression following injury, highlighting Otx2 as a potential target for further investigation and manipulation. These results provide insight into the molecular response to brain injury and suggest a potential link between developmental pathways and post-injury plasticity.